Should the JCPOA be Revived? An Analysis of the Iran Nuclear Deal - Yordan Gunawan; Aisyah Ajeng Putri Riyanto; Wandita Surya Putri; Cyabriena Asela; Dwilani Irrynta (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The Joint Comprehensive Plan of Action (JCPOA) is referred to as one the peaceful settlement of the international dispute in the form of a multilateral agreement restricting Iran's nuclear development in exchange for the lifting of economic sanctions. However, some issues have emerged since the agreement entered into effect. The United States withdrew from the agreement and reimposed the economic sanctions against Iran, consequently affecting Iran’s commitment to its nuclear obligations. State Parties' initiative to reinstate the agreement in its original form is invalid under international law since the issue is Iran and the United States' actions. In this research, the authors examined the termination and establishment of a new agreement as a strategy to overcome existing issues. The research methodology combines qualitative research with normative legal research. The results showed that the JCPOA is a